The evil demon in the lab: skepticism, introspection, and introspection of introspection. - Silins, Nicholas (Synthese, 2021)
In part one, I clarify the crucial notion of "introspection", and give novel cases for the coherence of scenarios of local and global deception about how we access our own minds, drawing on empirical work. In part two, I evaluate a series of skeptical arguments based on such scenarios of error, and in each case explain why the skeptical argument fails. The first main upshot is that we should not over-estimate what it takes to introspect: introspection need not be accurate, or non-inferential, or exclusive of perception, or even exclusive of confabulation. The second main upshot is that, while skeptical challenges by figures such as Carruthers, Doris, and Schwitzgebel are rich and empirically informed, these skeptical challenges founder on how they are epistemologically under-informed.